Francofonia [videorecording (DVD)] - Sokurov, Aleksandr, 1951-; Lencquesaing, Louis-Dominique de; Utzerath, Benjamin, 1963-; Nemeth, Vincent (Music Box Films, 2016)
Explore the Louvre Museum and the relevant meditation on the essential relationship between art, culture, and history.